A method for preparing a lightweight insulating column
By introducing inorganic microspheres and fibers into the insulating material and using ultrasonic vibration technology to prepare periodic nano microporous structures on the surface of aluminum alloy insert nuts, the problem of low anchoring force between traditional BMC materials and anodized aluminum is solved, and the problem of low anchoring force between traditional BMC materials and anodized aluminum is realized. High reliability lightweight insulating column preparation.
Patent Information
- Application Number
- CN202411443820.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The anchoring force of the periodic micropore interface between traditional BMC materials and anodized aluminum is low, resulting in insufficient anchoring ability of lightweight insulating columns.
Periodic nano microporous structures are prepared by introducing a combination of inorganic microspheres and inorganic fibers into the insulating material, and E-treated on the surface of the aluminum alloy insert nut. Combined with ultrasonic vibration technology, the inorganic filler is directionally vibrated and separated to form a blank area , avoid micropore blockage and improve the resin's ability to enter micropores, thereby enhancing anchoring capabilities.
High reliability lightweight insulating column preparation is achieved, which improves anchoring capacity while maintaining the lightweight properties of the material and improving mechanical properties.
Smart Images

Figure CN118969417B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of insulating materials, and in particular relates to a method for preparing a lightweight insulating column. Background Art
[0002] In the technical composition of flying cars, the safety and efficiency of the electrical system are key factors. Flying cars rely on high-efficiency electrical systems to provide power and control, which include components such as motors, battery packs, power distribution systems, and flight control systems. These components will generate high voltage and current during operation, so high-performance insulating materials are required to ensure the safe operation of the system and prevent arcing and short circuits. As a key component of the electrical system, the performance of the insulating column directly affects the overall safety and reliability of the flying car.
[0003] Under the premise of ensuring the reliability of electrical performance, the structural design of flying cars also pursues lightweighting to improve endurance and load efficiency. The use of composite materials and advanced insulation materials can effectively reduce the weight of the aircraft while maintaining structural strength and rigidity. The lightweighting of insulating columns plays an important role in this process, not only providing the necessary electrical insulation, but also supporting the lightweight goal of flying cars through their design.
[0004] Mainstream metal composite materials use copper alloy, galvanized carbon steel and aluminum alloy as insert nut materials. Among them, copper alloy and galvanized carbon steel have significantly stronger bonding ability than aluminum alloy, but their density is relatively large, which affects the lightweight design of the insulating column. The density of aluminum alloy is much lower than the former two, but due to its metal characteristics, its bonding force with resin is weak. In order to solve this problem, T treatment or E treatment is usually used for surface roughening or microporation, so as to improve the anchoring ability of the resin substrate and the roughened interface during embedding molding. However, the Japan Advanced Industrial Science and Technology Research Institute found through aging experiments that the tensile strength of the experimental resin should have exceeded 100MPa, while the test specimens of the composite material bonded with the resin and the surface microporous aluminum alloy often broke at around 40MPa. In-depth analysis found that the resin entered the holes of tens of microns in size formed by chemical treatment on the metal surface without gaps, and these resins did not fall off when they were damaged. The part of the resin that was extremely close to the interface was broken. At the same time, when the aluminum alloy surface is anodized to allow the resin to bond with it, it is found that the resin sometimes stops halfway into the tiny holes formed on the surface of the oxide film. It is believed that the reason is that the chemical reaction that can generate enough energy does not occur, and the energy is not enough to completely fill the holes with resin.
[0005] There are many explorations in the existing technology to solve the problem of weak bonding between aluminum alloy and resin, such as:
[0006] CN107150463 A provides a double-layer anodic oxide film, wherein the lower oxide film is nano-micropores and the top oxide film is micro-micropores, and the double-layer structure provides a better physical anchoring effect.
[0007] CN111455428 A provides a secondary pore expansion technology, which first uses T treatment and then uses E treatment to prepare a pore size greater than 150nm, and can achieve an anchoring effect of a composite material with a shear force greater than 38MPa.
[0008] CN103448202A provides an aluminum alloy with an aqueous polymer modified anodized film, and the microporous surface is more suitable for chemical anchoring with a resin material after modification.
[0009] CN112440430 A provides a process for preparing anodized films, which can produce micropores with a pore size of 10-80 nm and a depth of 0.2-1 μm, and provide an anchoring effect of a composite material with a shear force greater than 35 MPa.
[0010] CN104626453A provides a double-layer three-dimensional hole structure, which is prepared by first performing E treatment and then T treatment. The three-dimensional structure provides a pore diameter greater than 1μm, a pore depth greater than 4μm, and a bonding force greater than 11MPa.
[0011] It can be found that more technical research is currently focused on the improvement of micropores, especially the use of large pores and deep holes to accommodate more resin substrates, in order to solve the problem of more fracture defects at the joints. In lightweight research, there is less research on how to ensure anchoring ability. At present, in the field of lightweight BMC insulating columns, aluminum alloy weight-reducing inserts are more commonly used to replace or reduce the amount of calcium carbonate and glass fiber added in insulating materials. However, no technical solution for replacing calcium carbonate with inorganic microspheres has been found. It is likely that after the inorganic microspheres are replaced, they are in direct contact with the aluminum alloy interface, resulting in blockage of micropores or direct contact of inorganic materials with the aluminum alloy interface, resulting in too many weak bonding defects on the interface, causing the product's anchoring ability to weaken.
[0012] Therefore, the purpose of the present invention is to solve the performance defect problem of low anchoring force at the periodic microporous interface between traditional BMC materials and anodized aluminum by improving the preparation process. Summary of the invention
[0013] In view of the problems in the related art, the present invention proposes a method for preparing a lightweight insulating column to overcome the above technical problems existing in the existing related art.
[0014] The technical solution of the present invention is achieved by introducing inorganic fillers of one or more combinations of inorganic microspheres and inorganic fibers and aluminum alloy insert nuts with E-treated periodic nano-micropore interfaces into the insulating material, and subjecting the aluminum alloy insert nuts to ultrasonic vibration during the preparation process. The inorganic fillers close to the periodic nano-micropore interfaces are vibrated away through the directional vibration of the periodic nano-micropores to form an inorganic filler blank area, thereby avoiding micropore blockage or direct contact of the inorganic material with the aluminum alloy interface, and eliminating weak bonding defects at the interface. At the same time, ultrasonic vibration provides energy to realize the "cavitation effect", assists the resin to enter the periodic micropores of anodized aluminum, improves the anchoring ability of the resin and the micropores, and finally prepares a highly reliable lightweight insulating column. The specific contents of the invention are as follows:
[0015] A method for preparing a lightweight insulating column comprises an aluminum alloy insert nut and an insulating material.
[0016] Preferably, the insulating material consists of a resin base material, auxiliary additives and inorganic fillers.
[0017] More preferably, the resin base material in the insulating material is 18 to 28 parts of unsaturated polyester resin, the auxiliary additives are 5 to 15 parts of low shrinkage agent, 0.1 to 1 part of initiator, 1 to 3 parts of release agent, 0.1 to 0.5 parts of colorant, 15 to 35 parts of flame retardant, 15 to 25 parts of inorganic fiber, and 15 to 35 parts of inorganic microspheres.
[0018] More preferably, the resin substrate is one of o-phthalic acid, isophthalic acid, bisphenol A, and neopentyl glycol type unsaturated polyester resins.
[0019] More preferably, the initiator is one or more of alkyl hydroperoxides, dialkyl peroxides, diacyl peroxides, peresters, diester peroxycarbonates, and azo compounds.
[0020] More preferably, the initiator is one of TBIC, TBPB, BPO, LPS256 and LPS259.
[0021] More preferably, the low shrinkage agent is composed of one or more of PE, PVC copolymer, PMMA, PVAC, and PS.
[0022] More preferably, the flame retardant is aluminum hydroxide with a particle size of 5 to 20 μm.
[0023] More preferably, the colorant is one or more of carbon black or black nano-silicon dioxide with a particle size greater than 200 nm.
[0024] More preferably, the release agent is composed of one or more of zinc stearate and calcium stearate.
[0025] Preferably, the aluminum alloy insert nut is coated or bonded with the insulating material.
[0026] More preferably, the surface of the aluminum alloy insert nut after E treatment has a periodic nano-microporous structure with a pore diameter of 50 to 200 nm and a pore depth of 200 to 800 nm.
[0027] More preferably, the aluminum content of the aluminum alloy insert nut is greater than 96%.
[0028] More preferably, the aluminum alloy insert nut is made of 6061 aluminum alloy or 6063 aluminum alloy.
[0029] The present invention also discloses a method for preparing a lightweight insulating column, which is characterized by comprising the following steps:
[0030] S1: Prepare the aluminum alloy insert nut, first cut the initial profile of the insert nut, cut the groove band at the waistline of the outer surface of the initial profile, and then prepare the outer surface periodic nano-microporous structure by E treatment, phosphoric acid oxidation, voltage 0.015V / mm 2 , the oxidation temperature is 50°C, the oxidation time is 20 to 50 minutes, and finally a circular inner hole is opened at one end of the initial profile, and an internal thread is processed in the hole;
[0031] S2: preparing a premix of insulating material, adding the resin base material and auxiliary additives in a high-speed mixer at 800-1500 r / min in sequence and stirring evenly, ensuring that the mixing temperature is lower than 50°C, and the total mixing time is 30-45 minutes to obtain a resin premix slurry, adding the resin premix slurry to a kneader, adding inorganic microspheres and stirring for 30-45 minutes, and then evenly adding inorganic fibers, kneading and stirring for 10-15 minutes, pouring out the mass, extruding it into strips with an extruder, and then drying and chopping it into a product;
[0032] S3: After mechanical polishing, alkali washing, water washing and cold air drying of the aluminum alloy insert nuts prepared in step S1, two are placed in a group, concentrically axially, at a fixed interval and with opposite opening ends, into a mold, and then two groups A and B of torsional vibration ultrasonic transducer vibration heads coated with a coupling agent with a thickness of 0 to 1 mm are placed;
[0033] S4: Preheat the mold in S3, inject the pre-melted insulating material premix, and heat it to the curing temperature at a constant speed. During the heating period, the A and B ultrasonic transducers apply 20-40 MHz ultrasonic waves perpendicular to the direction of the vibration head, and apply a pressure of 3-14 MPa. The curing time is 1-2 mm insulating material thickness per minute, and the mold is demoulded after cooling by 5-15°C.
[0034] Preferably, the number of cutting groove bands at the waistline of the outer surface of the initial profile is greater than or equal to 1, and the sum of the widths of the groove bands is less than the length of the aluminum alloy insert nut.
[0035] Preferably, the width of the groove band is greater than the depth of the groove band, and the depth of the groove band is less than 1 / 2 of the thickness of the aluminum alloy insert nut.
[0036] Preferably, the inorganic microspheres are composed of one or more of silicon dioxide, silicon carbide, aluminum oxide, and mullite.
[0037] More preferably, the wall thickness of the inorganic microspheres is 1 / 5 to 1 of the particle size of the microspheres, and the particle size of the inorganic microspheres is larger than the pore size of the periodic nanopores.
[0038] Preferably, the inorganic fiber is one or more of glass fiber, quartz glass fiber, basalt fiber, alumina fiber, and mullite fiber.
[0039] More preferably, the inorganic fibers are hollow.
[0040] More preferably, the diameter of the inorganic fiber is larger than the diameter of the periodic nanopores, and the length is larger than 1 μm.
[0041] Preferably, the two groups A and B of torsional vibration ultrasonic transducer vibration heads are placed in an aluminum alloy kit, the inner wall of the aluminum alloy kit is smooth, and the outer wall thread size matches the inner thread of the aluminum alloy insert nut.
[0042] More preferably, the vibration phases of the two groups A and B of torsional vibration ultrasonic transducer vibration heads differ by 30 to 45 degrees.
[0043] More preferably, when the vibration heads of the two groups A and B of torsional vibration type ultrasonic transducers are inserted into the aluminum alloy insert nut or the aluminum alloy kit, the surfaces are coated with a coupling agent with a thickness of 0 to 1 mm.
[0044] More preferably, the ultrasonic coupling agent is one of glycerol, propylene glycol, polyethylene glycol, and methyl silicone oil.
[0045] Preferably, the vibration amplitude of the ultrasonic transducer is between 10 μm and 50 μm.
[0046] More preferably, the vibration amplitude of the ultrasonic transducer is between 20 μm and 30 μm.
[0047] Preferably, the insulating material is one of unsaturated polyester molding compound, epoxy molding compound, phenolic molding compound and amino molding compound.
[0048] Preferably, the kneader is a sigma kneader.
[0049] Preferably, the mixer is a Z-type reamer mixer or a planetary mixer.
[0050] Preferably, the applied pressure is 3-14 MPa.
[0051] More preferably, the applied pressure is 7-10 MPa.
[0052] Preferably, the mold preheating temperature is between 125°C and 140°C.
[0053] More preferably, the mold preheating temperature is between 130°C and 135°C.
[0054] Preferably, the curing temperature is 145-180°C.
[0055] Preferably, the demoulding temperature is 5-15° C. lower than the curing temperature.
[0056] Preferably, the curing time is calculated and set according to the wall thickness of the insulating material, and the curing speed is 1 to 2 mm / min.
[0057] More preferably, the curing speed is 1 to 1.5 mm / min.
[0058] Beneficial effects of the present invention:
[0059] Compared with the prior art, the present invention improves the preparation method of the traditional high-density metal composite insulating column, uses aluminum alloy instead of copper and copper alloy, and carbon steel materials to prepare the insert nut, uses low-density materials such as silica and alumina to replace calcium carbonate, and further uses hollow microspheres for lightweight design.
[0060] Furthermore, the present invention improves the preparation process to address the defect of smooth surface of traditional aluminum alloys and the defect that periodic nano-pores prepared on the surface of aluminum alloys are easily blocked by inorganic microspheres and inorganic fibers or directly contacted to cause weak bonding. By introducing torsional vibration ultrasound and using periodic nano-pores for ultrasonic directional propagation, the inorganic material is vibrated away from the pores, thereby eliminating the weak bonding defect.
[0061] Furthermore, the torsional vibration ultrasound introduced in the present invention also provides vibration energy to strengthen the "cavitation effect" for the large pore depth ratio of the periodic nano-micropores treated by E, assisting the resin to fully enter the pores, reducing the holes and improving the anchoring ability.
[0062] Ultimately, the preparation of lightweight insulating columns is achieved while improving mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0064] Figure 1 A schematic side view of the insulating column structure prepared in Example 1 of the present invention;
[0065] Figure 2 A schematic side view of an insulating column structure prepared in Example 2 of the present invention;
[0066] Figure 3 A schematic side view of an insulating column structure prepared in Example 3 of the present invention;
[0067] Figure 4 A schematic side view of an insulating column structure prepared in Example 4 of the present invention;
[0068] Figure 5 A schematic side view of an insulating column structure prepared in Example 5 of the present invention;
[0069] Figure 6 A schematic side view of the carbon steel insulating column structure prepared in Comparative Example 1 of the present invention;
[0070] Figure 7 It is a schematic top view of the insulating column structure prepared in Examples 1 to 5 of the present invention;
[0071] Figure 8 An electron micrograph of the blank area of inorganic filler of the insulating column aluminum alloy and the insulating material contact layer prepared by the present invention;
[0072] Fig. 9 A typical structural diagram of anodized periodic nano-micropores prepared by the present invention;
[0073] Among them, 1-ultrasonic vibration head, 2-insulating material, 3-inorganic filler blank filling area, 4-aluminum alloy insert nut, 5-ultrasonic coupling agent layer, 6-aluminum alloy nut kit, 7-carbon steel insert nut. DETAILED DESCRIPTION
[0074] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0075] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0076] In the present invention, the aluminum alloy is subjected to E treatment to prepare periodic micropores, and the periodic micropores prepared have a pore size of 50 to 200 nm, a depth of 200 to 800 nm, and a pore depth ratio of 4 to 5. The process is only a further implementation of the embodiment of the present invention, and any aluminum alloy profile with periodic micropores that meets the specifications prepared by E treatment but using different process conditions can be used in the present invention. The specific preparation conditions are as follows:
[0077] The aluminum alloy material with an aluminum content exceeding 96% is machined to prepare the initial profile of the aluminum alloy insert nut, and the initial profile is cold-dried after alkali washing and deionized water washing. The E treatment power supply adopts a KXN-3010D type voltage-stabilized DC power supply, with the initial profile as the anode and the carbon rod as the cathode, and a concentration of 15% H 3 PO 4 The solution is used as an electrolyte for anodization. During the anodization process, the voltage is maintained at 0.015V / mm 2 Constant, the temperature remains constant at 50 ℃, and the anodizing time is 20-50min. 3 PO 4 After anodization in the solution, the samples were cleaned with deionized water in an ultrasonic cleaner and dried with cold air. Fig. 9 .
[0078] In the present invention, the raw materials are mixed, stirred and extruded to prepare a bulk molding compound premix containing inorganic fillers, which is used for mold injection molding of aluminum alloy insert nuts. Under the condition that the inorganic filler is a combination of one or two inorganic microspheres and inorganic fibers, the change of the raw materials does not affect the technical effect of the present invention and can be used for bonding insulating materials and aluminum alloys to prepare the lightweight insulating column of the present invention. The specific process steps are as follows:
[0079] The resin base material and auxiliary additives are added to a high-speed mixer at 800-1500 r / min in sequence and stirred evenly, ensuring that the mixing temperature is below 50°C and the total mixing time is 30-45 minutes to obtain a resin premix slurry. The premix slurry is added to a sigma kneader, and inorganic microspheres are added and stirred for 30-45 minutes, and then inorganic fibers are evenly added, and a Z-type reamer mixer or a planetary mixer is used to stir for 10-15 minutes, and the mass is poured out, extruded into strips by an extruder, and chopped after drying.
[0080] Embodiments 1 to 5 of the present invention are products prepared by different preparation methods of lightweight insulating columns. Comparative Example 1 is an insulating column prepared using a carbon steel insert nut, Comparative Example 2 is a lightweight insulating column without ultrasonic vibration, and Comparative Example 3 is a lightweight insulating column without microsphere addition.
[0081] Embodiment 1, preparation of lightweight insulating column, comprises the following steps:
[0082] S1: Prepare the aluminum alloy insert nut 4, use 6063 aluminum alloy material, cut and prepare the initial profile of the insert nut with a diameter of Φ12mm and a length of 20mm, cut a groove band with a depth of 1mm and a width of 5mm at the waistline of the outer surface of the initial profile, and then 3 PO 4 The periodic microporous structure on the outer surface was prepared by E treatment under the conditions of solution, voltage of 15V, solution temperature of 50℃ and oxidation time of 30min. Finally, an inner hole of Φ8mm with a wall thickness of 2mm was opened at one end of the initial profile, and an internal thread was processed in the hole;
[0083] S2: Prepare a premix of insulating material, wherein the raw materials are 20 parts of resin base material, 1 part of medium-temperature initiator, 8 parts of low shrinkage agent, 2 parts of release agent, 0.5 parts of colorant, and 30 parts of flame retardant, which are sequentially added into a 1200r / min high-speed mixer and mixed for 30 minutes to prepare a premix slurry, and the premix slurry is added into a sigma kneader, 15 parts of inorganic microspheres are added and stirred for 40 minutes, and then 15 parts of inorganic fiber are added, and the mixture is mixed in a Z-type reamer mixer for 10 minutes, and then the mass is poured out, extruded by a 700r / min extruder, and crushed after cooling;
[0084] S3: After mechanical polishing, alkali washing, water washing and cold air drying of the aluminum alloy insert nuts prepared in step S1, two are placed in a group with concentric axes, 10 mm apart and opposite opening ends into the mold. The mold preparation product size is shown in Figure 1 As shown, two cylindrical ultrasonic transducer vibration heads 1 with an outer diameter of Φ7 mm, A and B, are simultaneously inserted into the aluminum alloy insert nut, and an ultrasonic coupling agent layer 5 is filled in the gap between the ultrasonic transducer and the aluminum alloy insert nut;
[0085] S4: The mold in S3 is preheated to 135℃, and the premix of pre-melted insulating material at 80℃ is injected into the mold with an injection pressure of 1.5MPa. The mold cavity is heated to 145℃ at a rate of 5℃ / min. During the heating period, 20MHz ultrasonic waves perpendicular to the direction of the vibration head are applied by torsional vibration. The torsional vibration phases of the two vibration heads A and B differ by 45°. During the heating period, a pressure of 7MPa is applied, the curing time is 5min, and the mold is demoulded after the temperature is lowered by 10℃.
[0086] The resin substrate used in the preparation of this embodiment is o-phthalic unsaturated polyurethane, the initiator is medium-temperature TBPO, the low shrinkage agent is LS, the release agent is zinc stearate ZnSt, the inorganic filler particle size is 2μm hollow alumina microspheres, the inorganic fiber is 6mm short glass fiber, the colorant is 200nm carbon black, the flame retardant is 20μm aluminum hydroxide, and the ultrasonic coupling agent is methyl silicone oil. The maximum amplitude of the ultrasonic wave is 35μm, and the working amplitude is 30%. Ultrasonic vibration is used to achieve the periodic microporous interface of the inorganic filler 4 to form an inorganic filler blank filling area 3.
[0087] Embodiment 2, preparation of lightweight insulating column, comprises the following steps:
[0088] S1: Prepare the aluminum alloy insert nut 4, use 1060 aluminum alloy material, cut and prepare the initial profile of the insert nut with a diameter of Φ12mm and a length of 20mm, cut a groove band with a depth of 1mm and a width of 3mm at the waistline of the outer surface of the initial profile, and then 3 PO 4 The periodic microporous structure on the outer surface was prepared by E treatment under the conditions of solution, voltage of 15V, solution temperature of 50℃ and oxidation time of 35min. Finally, an inner hole of Φ8mm with a wall thickness of 2mm was opened at one end of the initial profile, and an internal thread was processed in the hole;
[0089] S2: Prepare insulating material premix, the raw materials are 25 parts of resin base material, 0.1 parts of high temperature initiator, 0.6 parts of medium temperature initiator, 8 parts of low shrinkage agent, 2 parts of release agent, 0.5 parts of colorant, 35 parts of flame retardant, add them in a 1200r / min high-speed mixer and mix for 30 minutes to prepare premix slurry, add the premix slurry into a sigma kneader, add 20 parts of inorganic microspheres and stir for 40 minutes, then add 18 parts of inorganic fiber, mix in a Z-type reamer mixer for 10 minutes, pour out the mass, extrude it with a 700r / min extruder, and grind it after cooling;
[0090] S3: After mechanical polishing, alkali washing, water washing and cold air drying of the aluminum alloy insert nut 4 prepared in step S1, a conformal aluminum alloy set 6 with a smooth inner wall, a threaded outer wall, a wall thickness of 2 mm and an inner diameter of 6 mm is embedded in the aluminum alloy insert nut 4. Two sets are placed in a mold with concentric axes, a spacing of 10 mm and opposite opening ends. The product structure is shown in FIG. Figure 2 As shown, two conformal ultrasonic transducer vibration heads 1, A and B, with an outer diameter of Φ6 mm are then placed in the aluminum alloy kit 6;
[0091] S4: The mold in S3 is preheated to 130℃, and the premix of pre-melted insulating material at 80℃ is injected into the mold with an injection pressure of 2MPa. The temperature is then raised to 150℃ at 10℃ / min. During the heating period, 30MHz ultrasonic waves perpendicular to the direction of the vibration head are applied by torsional vibration. The torsional vibration phases of the two vibration heads A and B differ by 30°. A pressure of 10Mpa is applied during the heating period. The curing time is 5min, and the mold is demolded after the temperature is lowered by 15℃.
[0092] The resin substrate used in the preparation of this embodiment is isophthalic unsaturated polyurethane, the high temperature initiator is TBPB, the medium temperature initiator is TBPO, the low shrinkage agent is LPA, the release agent is zinc stearate ZnSt, the inorganic filler particle size is 5μm hollow mullite microspheres, the inorganic fiber is 6mm short chopped quartz glass fiber, the colorant is 200nm black silica microspheres, the flame retardant is 10μm aluminum hydroxide, and the ultrasonic transducer vibration head can also be coated with ultrasonic coupling agent propylene glycol for micro-filling. The maximum amplitude of the ultrasonic wave is 35μm, and the working amplitude is 40%.
[0093] Embodiment 3, preparation of lightweight insulating column, comprises the following steps:
[0094] S1: Prepare the aluminum alloy insert nut 4, use 1060 aluminum alloy material, cut and prepare the initial profile of the insert nut with a diameter of Φ12mm and a length of 20mm, cut three grooves with a depth of 1mm and a width of 2mm at the waistline of the outer surface of the initial profile, and then 3 PO 4The periodic microporous structure on the outer surface was prepared by E treatment under the conditions of solution, voltage of 15V, solution temperature of 50℃ and oxidation time of 38min. Finally, an inner hole of Φ8mm with a wall thickness of 2mm was opened at one end of the initial profile, and an internal thread was processed in the hole;
[0095] S2: Prepare insulating material premix, the raw materials are 18 parts of resin base material, 0.3 parts of high temperature initiator, 0.5 parts of medium temperature initiator, 10 parts of low shrinkage agent, 1 part of release agent, 28 parts of flame retardant, 0.1 parts of colorant, add them in turn in a 1200r / min high-speed mixer and mix for 30 minutes, add the premixed slurry into a sigma kneader, add 20 parts of inorganic microspheres and stir for 40 minutes, then add 20 parts of inorganic fiber and mix in a Z-type reamer mixer for 10 minutes, pour out the mass, extrude it in a 700r / min extruder, and grind it after cooling;
[0096] S3: After mechanical polishing, alkali washing, water washing and cold air drying of the aluminum alloy insert nut 4 prepared in step S1, a conformal aluminum alloy set 6 with a smooth inner wall, a threaded outer wall, a wall thickness of 2 mm and an inner diameter of 6 mm is embedded in the aluminum alloy insert nut 4. Two sets are placed in a mold with concentric axial directions, a spacing of 10 mm and opposite opening ends. The product size is shown in the figure. Figure 3 As shown, two conformal ultrasonic transducer vibration heads 1, A and B, with an outer diameter of Φ6 mm are then placed in the aluminum alloy kit 6;
[0097] S4: The mold in S3 is preheated to 130℃, and the premix of pre-melted insulating material at 80℃ is injected into the mold with an injection pressure of 1.4MPa. The temperature is then raised to 145℃ at 5℃ / min. During the heating period, 30MHz ultrasonic waves perpendicular to the direction of the vibration head are applied by torsional vibration. The torsional vibration phases of the two vibration heads A and B differ by 40°. During the heating period, 5MPa is applied as the pressure, the curing time is 5min, and the mold is demolded after the temperature is lowered by 10℃.
[0098] The resin substrate used in the preparation of this embodiment is bisphenol A type unsaturated polyurethane, the high temperature initiator is TBPB, the medium temperature initiator is TBPO, the low shrinkage agent is LPA, the release agent is zinc stearate ZnSt, the inorganic filler particle size is 600nm hollow silica microspheres, the inorganic fiber is 6mm short chopped basalt fiber, the colorant is 200nm carbon black, the flame retardant is 15μm aluminum hydroxide, and the ultrasonic transducer vibration head can also be coated with ultrasonic coupling agent glycerol for micro-filling. The maximum amplitude of the ultrasonic wave is 40μm, and the working amplitude is 60%.
[0099] Embodiment 4, preparation of lightweight insulating column, comprises the following steps:
[0100] S1: Prepare the aluminum alloy insert nut 4, use 6061 aluminum alloy material, cut and prepare the initial profile of the insert nut with a diameter of Φ12mm and a length of 20mm, cut a groove band with a depth of 1mm and a width of 4mm at the waistline of the outer surface of the initial profile, and then 3 PO 4 The periodic microporous structure on the outer surface was prepared by E treatment under the conditions of solution, voltage of 15V, solution temperature of 50℃ and oxidation time of 10min. Finally, an inner hole of Φ8mm with a wall thickness of 2mm was opened at one end of the initial profile, and an internal thread was processed in the hole;
[0101] S2: Prepare insulating material premix, the raw materials are 18 parts of resin base material, 0.6 parts of high temperature initiator, 0.2 parts of medium temperature initiator, 15 parts of low shrinkage agent, 1 part of release agent, 0.2 parts of colorant, 15 parts of flame retardant, add them in turn in a 1200r / min high-speed mixer and mix for 30 minutes, then add 20 parts of A inorganic microspheres and 5 parts of B inorganic microspheres, knead them in a sigma kneader for 30 minutes, then add 18 parts of inorganic fiber, mix in a Z-type reamer mixer for 10 minutes, pour out the mass, extrude it in a 700r / min extruder, and grind it after cooling;
[0102] S3: After mechanical polishing, alkali washing, water washing and cold air drying of the aluminum alloy insert nut 4 prepared in step S1, a conformal aluminum alloy set 6 with a smooth inner wall, a threaded outer wall, a wall thickness of 2 mm and an inner diameter of 6 mm is embedded in the aluminum alloy insert nut 4. Two sets are placed in a mold with concentric axes, a spacing of 10 mm and opposite opening ends. The product structure is shown in FIG. Figure 4 As shown, two conformal ultrasonic transducer vibration heads 1, A and B, with an outer diameter of Φ6 mm are then placed in the aluminum alloy kit 6;
[0103] S4: The mold in S3 is preheated to 135℃, and the premix of pre-melted insulating material at 90℃ is injected into the mold with an injection pressure of 1.8MPa. The temperature is then raised to 155℃ at 5℃ / min. During the heating period, 40MHz ultrasonic waves perpendicular to the direction of the vibration head are applied by torsional vibration. The torsional vibration phases of the two vibration heads A and B differ by 30°. During the heating period, the pressure is 12Mpa, the curing time is 5min, and the mold is demolded after the temperature is lowered by 15℃.
[0104] The resin substrate used in the preparation of this embodiment is neopentyl glycol type unsaturated polyurethane, the high temperature initiator is TBPB, the medium temperature initiator is TBPO, the low shrinkage agent is LPA, the release agent is zinc stearate ZnSt, the inorganic filler A is hollow silica microspheres with a particle size of 800nm, the inorganic filler B is black hollow silica microspheres with a particle size of 200nm, the inorganic fiber is 6mm short basalt fiber, and the flame retardant is 5μm aluminum hydroxide. The ultrasonic transducer vibration head can also be coated with ultrasonic coupling agent methyl silicone oil for micro-filling. The maximum amplitude of the ultrasonic wave is 35μm, and the working amplitude is 60%.
[0105] Embodiment 5, preparation of lightweight insulating column, comprises the following steps:
[0106] S1: Prepare the aluminum alloy insert nut 4, use 6061 aluminum alloy material, cut and prepare the initial profile of the insert nut with a diameter of Φ12mm and a length of 20mm, cut three grooves with a depth of 1mm and a width of 2mm at the waistline of the outer surface of the initial profile, and then 3 PO 4 The periodic microporous structure on the outer surface was prepared by E treatment under the conditions of solution, voltage of 15V, solution temperature of 50℃ and oxidation time of 10min. Finally, an inner hole of Φ8mm with a wall thickness of 2mm was opened at one end of the initial profile, and an internal thread was processed in the hole;
[0107] S2: Prepare the premix of insulating material, the raw materials are 18 parts of resin base material, 0.7 parts of medium temperature initiator, 5 parts of low shrinkage agent, 1 part of release agent, 0.2 parts of colorant, 20 parts of flame retardant, add them in a 1200r / min high-speed mixer and mix for 35 minutes, then add 25 parts of A inorganic microspheres, then add 20 parts of inorganic fiber, knead with a sigma kneader for 35 minutes, mix in a Z-type reamer mixer for 10 minutes, pour out the mass, extrude with a 700r / min extruder, and grind and prepare the material after cooling;
[0108] S3: After mechanical polishing, alkali washing, water washing and cold air drying of the aluminum alloy insert nut 4 prepared in step S1, a conformal aluminum alloy set 6 with a smooth inner wall, a threaded outer wall, a wall thickness of 2 mm and an inner diameter of 6 mm is embedded in the aluminum alloy insert nut 4. Two sets are placed in a mold with concentric axes, a spacing of 5 mm and opposite opening ends. The product structure is shown in FIG. Figure 5 As shown, two conformal ultrasonic transducer vibration heads 1, A and B, with an outer diameter of Φ5.5 mm are then placed in the aluminum alloy kit 6;
[0109] S4: The mold in S3 is preheated to 135℃, and the premix of pre-melted insulating material at 80℃ is injected into the mold with an injection pressure of 1.8MPa. The temperature is then raised to 155℃ at 5℃ / min. During the heating period, 40MHz ultrasonic waves perpendicular to the direction of the vibration head are applied by torsional vibration. The torsional vibration phases of the two vibration heads A and B differ by 30°. During the heating period, the pressure is 12Mpa, the curing time is 5min, and the mold is demolded after the temperature is lowered by 15℃.
[0110] The resin substrate used in the preparation of this embodiment is o-phthalic unsaturated polyurethane, the medium temperature initiator is TBPO, the low shrinkage agent is LPA, the release agent is zinc stearate ZnSt, the inorganic filler particle size is 10μm solid calcium hydroxide microspheres, the inorganic fiber is 6mm short glass fiber, the colorant is 250nm carbon black, the flame retardant is 10μm aluminum hydroxide, and the ultrasonic transducer vibration head can also be coated with ultrasonic coupling agent methyl silicone oil for micro-filling. The maximum amplitude of the ultrasonic wave is 35μm, and the working amplitude is 50%.
[0111] Comparative Example 1: Prepare a carbon steel insulating column with a structure as follows Figure 6 , including the following steps:
[0112] S1: Prepare the carbon steel insert nut 7, cut and prepare the initial profile of the insert nut with a diameter of Φ12mm and a length of 20mm, cut a groove band with a depth of 1mm and a width of 5mm at the waistline of the outer surface of the initial profile, and finally open an inner hole of Φ8mm at one end of the initial profile with a wall thickness of 2mm, and process an internal thread in the hole;
[0113] S2: Prepare the premix of insulating material, the raw materials are 20 parts of resin base material, 0.8 parts of medium temperature initiator, 8 parts of low shrinkage agent, 0.8 parts of release agent, 0.3 parts of colorant, 20 parts of reinforcing agent and 30 parts of flame retardant, add them in a 1200r / min high-speed mixer and mix them, then add 18 parts of inorganic fiber, mix them in a Z-type reamer mixer for 10 minutes, pour out the mass, extrude it in a 700r / min extruder, and grind it into material after cooling;
[0114] S3: After mechanical polishing, alkali washing, water washing and cold air drying, the carbon steel insert nuts 7 prepared in step S1 are placed into a mold in groups of two with concentric axes, a spacing of 10 mm and opposite opening ends. The product dimensions are shown in the table below. Figure 6 As shown;
[0115] S4: The mold in S3 is preheated at 135°C, and the premix of the pre-melted insulating material at 80°C is injected into the mold with an injection pressure of 2MPa. The temperature is then raised to 145°C at a rate of 5°C / min. A pressure of 10MPa is applied during the heating period. The curing time is 5min, and the mold is demoulded after the temperature is lowered by 10°C.
[0116] The resin substrate used in the preparation of this embodiment is o-phthalic unsaturated polyurethane, the medium temperature initiator is TBPO, the low shrinkage agent is LPA, the release agent is zinc stearate ZnSt, the reinforcing agent is calcium carbonate microspheres with a particle size of 10 μm, the flame retardant is 10 μm aluminum hydroxide microspheres, the inorganic fiber is 6 mm short glass fiber, and the colorant is 200 nm carbon black.
[0117] Comparative Example 2, preparation of a lightweight insulating column, comprising the following steps:
[0118] S1: Prepare the aluminum alloy insert nut 4, use 6063 aluminum alloy material, cut and prepare the initial profile of the insert nut with a diameter of Φ12mm and a length of 20mm, cut a groove band with a depth of 1mm and a width of 5mm at the waistline of the outer surface of the initial profile, and then 3 PO 4 The periodic microporous structure on the outer surface was prepared by E treatment under the conditions of solution, voltage of 15V, solution temperature of 50℃ and oxidation time of 30min. Finally, an inner hole of Φ8mm with a wall thickness of 2mm was opened at one end of the initial profile, and an internal thread was processed in the hole;
[0119] S2: Prepare a premix of insulating material. The raw materials are 20 parts of resin base material, 0.5 parts of initiator, 8 parts of low shrinkage agent, 2 parts of release agent, 0.5 parts of colorant and 30 parts of flame retardant. Add them into a 1200r / min high-speed mixer and mix for 30 minutes to prepare a premix slurry. Add the premix slurry into a sigma kneader, add 15 parts of inorganic microspheres and stir for 40 minutes, then add 20 parts of inorganic fiber, mix in a Z-type reamer mixer for 10 minutes, pour out the mass, extrude it into an extruder at 700r / min, and grind it into material after cooling.
[0120] S3: After mechanical polishing, alkali washing, water washing and cold air drying, the aluminum alloy insert nuts prepared in step S1 are placed into a mold in groups of two with concentric axes, a spacing of 10 mm and opposite opening ends. The size of the mold product is the same as that in Example 1;
[0121] S4: The mold in S3 is preheated to 135℃, and the premix of pre-melted insulating material at 80℃ is injected into the mold with an injection pressure of 1.5MPa. The mold cavity is heated to 145℃ at 5℃ / min, and a pressure of 7MPa is applied during the heating period. The curing time is 5min, and the mold is demoulded after the temperature is lowered by 10℃.
[0122] The resin substrate used in the preparation of this embodiment is o-phthalic unsaturated polyurethane, the medium temperature initiator is TBPO, the low shrinkage agent is LS, the release agent is zinc stearate ZnSt, the inorganic filler particle size is 2μm hollow alumina microspheres, the inorganic fiber is 6mm short glass fiber, the colorant is 200nm carbon black, the flame retardant is 20μm aluminum hydroxide, and there is no blank filling area.
[0123] Comparative Example 3, preparation of a lightweight insulating column, comprising the following steps:
[0124] S1: Prepare the aluminum alloy insert nut 4, use 6063 aluminum alloy material, cut and prepare the initial profile of the insert nut with a diameter of Φ12mm and a length of 20mm, cut a groove band with a depth of 1mm and a width of 5mm at the waistline of the outer surface of the initial profile, and then 3 PO 4 The periodic microporous structure on the outer surface was prepared by E treatment under the conditions of solution, voltage of 15V, solution temperature of 50℃ and oxidation time of 30min. Finally, an inner hole of Φ8mm with a wall thickness of 2mm was opened at one end of the initial profile, and an internal thread was processed in the hole;
[0125] S2: Prepare a premix of insulating material, wherein the raw materials are 20 parts of resin base material, 0.5 parts of initiator, 8 parts of low shrinkage agent, 2 parts of release agent, 0.5 parts of colorant and 30 parts of flame retardant, which are sequentially added into a 1200r / min high-speed mixer and mixed for 30 minutes to prepare a premix slurry, and then 20 parts of inorganic fiber are added, mixed in a Z-type reamer mixer for 10 minutes, and then the mass is poured out, extruded by a 700r / min extruder, and crushed after cooling;
[0126] S3: After mechanical polishing, alkali washing, water washing and cold air drying of the aluminum alloy insert nuts prepared in step S1, two are placed in a group, coaxially, 10 mm apart and with opposite opening ends into a mold, the mold size is the same as that of Example 1, and then two conformal ultrasonic transducer vibration heads 1, A and B, with an outer diameter of Φ5.5 mm, are placed in the aluminum alloy kit 6;
[0127] S4: The mold in S3 is preheated to 135℃, and the premix of pre-melted insulating material at 80℃ is injected into the mold with an injection pressure of 1.5MPa. The mold cavity is heated to 145℃ at a rate of 5℃ / min. During the heating period, 20MHz ultrasonic waves perpendicular to the direction of the vibration head are applied by torsional vibration. The torsional vibration phases of the two vibration heads A and B differ by 45°. During the heating period, a pressure of 7MPa is applied, the curing time is 5min, and the mold is demoulded after the temperature is lowered by 10℃.
[0128] The resin substrate used in the preparation of this embodiment is o-phthalic unsaturated polyurethane, the medium temperature initiator is TBPO, the low shrinkage agent is LS, the release agent is zinc stearate ZnSt, the inorganic fiber is 6mm short glass fiber, the colorant is 200nm carbon black, the flame retardant is 20μm aluminum hydroxide, and the ultrasonic coupling agent is methyl silicone oil. The maximum amplitude of the ultrasonic wave is 35μm, and the working amplitude is 30%. The inorganic filler is vibrated away from the periodic microporous interface of the aluminum alloy insert nut 4 by ultrasonic vibration, forming an inorganic filler blank filling area 3.
[0129] The physical properties of Examples 1 to 5 and Comparative Examples 1 to 3 were tested and shown in Table 1:
[0130] Table 1
[0131]
[0132] By comparing the data in Table 1, it can be found that the addition of hollow inorganic microspheres in Example 3 significantly reduces the weight of the insulating column, up to 47%, while its torsion, tension, and shear force are not significantly reduced. In Example 5, because the addition of hollow microspheres improves the insulation performance of the material, the distance between the two insert nuts can be reduced, thereby further reducing weight and increasing various performances by about 10 to 30%. Comparative Example 1 did not perform ultrasonic vibration, and its anchoring ability was reduced by about 15 to 25%. The above vibration effect can be seen from Figure 8 It can be seen that there is an obvious blank filling boundary between the aluminum alloy and the insulating material. Therefore, the product prepared by the present invention significantly improves the overweight problem of the carbon steel insulating column, while avoiding the clogging of the anodized micropores by the inorganic microspheres. At the same time, ultrasonic vibration increases the micropore filling rate, and achieves obvious results in ensuring the anchoring force, providing a new technical solution for the aerospace field, which is more suitable for application in this field.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a lightweight insulating column, characterized in that: The lightweight insulating column comprises an aluminum alloy insert nut and an insulating material, wherein the aluminum alloy insert nut is coated or bonded by the insulating material, the outer surface of the aluminum alloy insert nut is subjected to E treatment to prepare periodic nano-micropores, the insulating material is composed of a resin substrate, an auxiliary additive and an inorganic filler, the insert nut and the insulating material are bonded or coated by an inorganic filler blank area formed by ultrasonic vibration of the inorganic filler, and the preparation of the lightweight insulating column comprises the following steps: S1: preparing the aluminum alloy insert nut, first cutting the initial profile of the insert nut, cutting a groove band at the waistline of the outer surface of the initial profile, then preparing a periodic nano-microporous structure on the outer surface by E treatment, and finally opening a circular inner hole at one end of the initial profile, and processing an internal thread in the hole; S2: preparing a premix of insulating material, adding the resin base material and auxiliary additives in a high-speed mixer at 800-1500 r / min in sequence and stirring evenly, ensuring that the mixing temperature is lower than 50°C, and the total mixing time is 30-45 minutes to obtain a resin premix slurry, adding the resin premix slurry to a kneader, adding inorganic microspheres and stirring for 30-45 minutes, and then evenly adding inorganic fibers, kneading and stirring for 10-15 minutes, pouring out the mass, extruding it into strips with an extruder, and then drying and chopping it into a product; S3: After mechanical polishing, alkali washing, water washing and cold air drying of the aluminum alloy insert nuts prepared in step S1, two are placed in a group, concentrically axially, at a fixed interval and with opposite opening ends, into a mold, and then two groups A and B of torsional vibration ultrasonic transducer vibration heads coated with a coupling agent with a thickness of 0 to 1 mm are placed; S4: Preheat the mold in S3, inject the pre-melted insulating material premix, and heat it to the curing temperature at a constant speed. During the heating period, the A and B ultrasonic transducers apply 20-40 MHz ultrasonic waves perpendicular to the direction of the vibration head, and apply a pressure of 3-14 MPa. The curing time is 1-2 mm insulating material thickness per minute, and the mold is demoulded after cooling by 5-15°C.
2. The method for preparing a lightweight insulating column according to claim 1, characterized in that: The pore diameter of the surface periodic nano-micropore structure after E treatment is 50-200nm, and the pore depth is 200-800nm.
3. The method for preparing a lightweight insulating column according to claim 1, characterized in that: The number of cut groove bands at the waistline of the outer surface of the initial profile is greater than or equal to 1, the total width of the groove bands is less than the length of the aluminum alloy insert nut, the width of the groove band is greater than the depth of the groove band, and the depth of the groove band is less than 1 / 2 of the thickness of the aluminum alloy insert nut.
4. The method for preparing a lightweight insulating column according to claim 1, characterized in that: The resin base material in the insulating material is 18 to 28 parts of unsaturated polyester resin, the auxiliary additives are 0.1 to 1 parts of initiator, 5 to 15 parts of low shrinkage agent, 15 to 35 parts of flame retardant, 1 to 3 parts of release agent, 0.1 to 0.5 parts of colorant, the inorganic fiber is 15 to 25 parts, and the inorganic microspheres are 15 to 35 parts.
5. The method for preparing a lightweight insulating column according to claim 4, characterized in that: The resin substrate is one of o-phthalate, isophthalate, bisphenol A, and neopentyl glycol type unsaturated polyester resins; the initiator is one or more of alkyl hydroperoxides, dialkyl peroxides, diacyl peroxides, peresters, peroxydicarbonates, and azo compounds; the low shrinkage agent is one or more of PE, PVC copolymer, PMMA, PVAC, and PS; the colorant is one or more of carbon black or black nano-silicon dioxide with a particle size greater than 200 nm; the release agent is one or more of zinc stearate and calcium stearate; and the flame retardant is aluminum hydroxide with a particle size of 5 to 20 μm.
6. The method for preparing a lightweight insulating column according to claim 4, characterized in that: The inorganic microspheres are composed of one or more of silicon dioxide, silicon carbide, aluminum oxide, aluminum hydroxide, and mullite; the inorganic fibers are composed of one or more of glass fibers, quartz glass fibers, basalt fibers, alumina fibers, and mullite fibers; the inorganic microspheres and inorganic fibers are composed of one or more of solid and hollow; and the size of the inorganic microspheres and inorganic fibers in any direction is greater than 200 nm.
7. The method for preparing a lightweight insulating column according to claim 1, characterized in that: The torsional vibration type ultrasonic transducer vibration head is coated with a coupling agent with a thickness of 0 to 1 mm and is placed in an aluminum alloy kit. The inner wall of the aluminum alloy kit is smooth, and the outer wall thread size matches the inner thread of the aluminum alloy insert nut.
8. The method for preparing a lightweight insulating column according to claim 1, characterized in that: The vibration phases of the two groups A and B of torsional vibration ultrasonic transducer vibration heads differ by 30 to 45 degrees.
Citation Information
Patent Citations
Preparation method of metal resin complex and metal resin complex prepared thereby
CN103448202A
Preparation method of aluminum alloy resin composite body and aluminum alloy resin composite body
CN104626453A
Metal resin complex and preparation technology thereof
CN107150463A
Aluminum alloy micro-pore-enlarging agent and surface treatment method of aluminum alloy material
CN111455428A
Resin-aluminum alloy complex, preparation method and shell
CN112440430A